MEKANISME PRAGMATIK DALAM PENCIPTAAN HUMOR; ANALISIS TERHADAP WACANA HUMOR SUNDA - Kurniati, Ai; Basori, B (Jurnal Tradisi Lisan Nusantara, 2023)
Abstract: Humor knows no social class and can come from various aspects of life. Humor is a way of giving birth to a thought, either in words (verbally) or in another way that describes an invitation that creates sympathy and entertainment. The data studied in this study came from the written variety of Sundanese. The data selected in this study are limited, namely verbal humor discourse, in terms of presentation it is written humor discourse, and in terms of topic it is a type of social humor. The data were taken from Sundanese humorous discourse, namely the book Kumpulan Guguyon Sabulangbentor 1–7 by Taufik Faturohman (2007). There are various violations of pragmatic principles, namely the principle of cooperation in the social humor data in question, including violations of the maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner. Violation of the cooperative principle is an attempt by the creator of humor to bring about a funny effect.